A Research Note on Age Discrimination and the Desire to Retire: The Mediating Effect of Psychological Empowerment. (May 2014) - Schermuly, Carsten C.; Deller, Jürgen; Büsch, Victoria
Age discrimination is a common problem in organizations. In our pilot study, we want to explore the processes how the desired retirement age is influenced by age discrimination and see psychological empowerment as an important mediator for the relationship between these variables. Data stem from an online questionnaire completed by 130 employees from different organizations in Germany (all 50 years or older). Our results show that age discrimination is an antecedent for the desired retirement age. It has a direct as well as an indirect (via psychological empowerment) effect on the desired retirement age.